PENGARUH UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA TERHADAP TENAGA KERJA DI INDONESIA - Gultom, Ricky Ignatius Sadana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Law Number 11 of 2020 Concerning Job Creation is a law enacted by the state legislature, namely the People's Legislative Council, which has the objective of essentially forming the government of the State of Indonesia and realizing a prosperous, just and prosperous Indonesian society based on Pancasila and the constitution of the Republic of Indonesia. Which in completing this article, the research method used is legal research with the type of normative juridical research. The workers continue to highlight the performance of the DPR and the government with the speedy discussion of the work copyright omnibus law. One of them is the issue of contract employees and outsourcing for life, without time limit and type of work. The job creation law, which has reaped its pros and cons after the existence of this law, is expected to attract many foreign investors to start investing in Indonesia.